Chief Executive Officer Compensation and Financial Performance: Evidence from the Alternative Investment Market in the UK. Issue 1 (June 2020) - Jeff Boakye, Danquah; Sam Ahinful, Gabriel; Nsor-Ambala, Randolph
Abstract: Purpose: This article investigates the relationship between executive compensation and financial performance for Alternative Investment Market (AIM)-listed firms in the UK. While most studies have looked at the impact of executive compensation on financial performance, this study argues that the issue of reverse causality cannot be ignored even if it is controlled and therefore investigates the extent to which financial performance can also impact on executive remuneration. Design/methodology/approach: The study relies on a sample of 201 AIM-listed firms in the UK from 2011 to 2016 to examine the relationship between executive compensation and financial performance. It draws on agency and tournament theories to model the relationships between executive compensation and financial performance using various panel regression models. Findings: The findings from the study revealed that the chief executive officer (CEO) remuneration impact on both accounting- and market-based measures of financial performance. It also showed that while performance-based incentives like bonus and other long-term incentives linked to performance significantly impact on financial performance, salary, a cash-based non-performance-related compensation rather negatively affects performance. It was also discovered that financial performance can also influence the level of executive compensation and not always vice versa. Value/originality: The study adds novelties to the existing literature by introducing tournament theory to the studies on the relationship between executive compensation and financial performance. Most of the existing studies have been one sided and emphasise only on the influence of executive remuneration on financial performance. However, based on the tournament theory, the study argued that the issue of reverse causality between the two should not be overemphasised even if it is controlled.